Advancement of optical methods & digital image correlation in experimental mechanics. proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics. Volume 3 : ([2019]) - Unknown
No abstract available